Neoliberalism And Contemporary Literary Culture - Huehls, Mitchum and Smith, Rachel Greenwald (John Hopkins University Press, 2017)
This book offers a wide-ranging exploration of contemporary literature through the lens of neoliberalism's economic, social, and cultural ascendance.